Hilangnya Budaya Lokal di Era Modern dan Upaya Pelestariannya dalam Perspektif Pancasila - Aisya Putri Handayani; Jap Tji Beng; Febynola Tiara Salsabilla; Stefania Morin; Thalia Syahrunia Suci Ardhia; Valensia Audrey Rusli (Universitas 45 Surabaya, 2024)
Globalization phenomena influx a foreign culture, can shift the local cultural order. For example: K-pop culture increasingly dominates the preferences of young people, and reduces appreciation of local cultures. The loss of local culture and the declining application of Pancasila values pose a serious threat to the identity and sustainability of the nation. Pancasila serve a foundation of national life that is able to strengthen national identity in the midst of various global challenges. This research aims to analyze the impact of modernization and globalization on the loss of local culture in Indonesia, as well as the role of Pancasila in its preservation. This research uses qualitative methods with interview technique. The results of this study reveal that respondents have a good understanding of the concepts of modernization and globalization. Some respondents also realize that modernization and globalization can erode local cultural identity if not balanced with appropriate preservation efforts. From this research, it can be concluded that modernization and globalization can bring more impact or influence on local culture in Indonesia. The application of the precepts in Pancasila is believed to help maintain a balance between openness to global culture and preservation of national identity.